Analisis Pengaruh Kinerja Keuangan terhadap Pengeluaran Dana Zakat Perusahaan pada Bank Umum Syariah - Sinta Fitria; Dimas Sumitra Danisworo; Miftahurrohman Miftahurrohman; Myra Andriana (Journal of Applied Islamic Economics and Finance, 2022)
This study aims to analyze the effect of Return on Asset, Non-Performing Financing, Financing to Deposit Ratio, and Capital Adequacy Ratio on the expenditure of corporate zakat funds at Islamic Commercial Banks for the 2014-2020 period. The data used is secondary data, namely annual financial report data published on the official website of each bank which is collected through documentation techniques in the form of documents and other financial reports related to this research. The number of samples used in this study was six of 14 Islamic Commercial Banks. The sampling technique used the purposive sampling technique. The analytical method used is panel data regression analysis with Eviews version 9. The results of this study indicate that the ROA and FDR have a significant effect on the expenditure of zakat funds in Islamic Commercial Banks. Meanwhile, NPF and CAR partially have no significant effect on the expenditure of zakat funds in Islamic Commercial Banks. Simultaneously ROA, NPF, FDR, and CAR have an effect on the company's zakat funds disbursement at Islamic Commercial Banks.